A comparative study of continuous beams prestressed with bonded FRP and steel tendons. (June 2015) - Lou, Tiejiong; Lopes, Sergio M.R.; Lopes, Adelino V.
Abstract: This paper presents a numerical investigation of the performance of continuous prestressed concrete beams with bonded fiber reinforced polymer (FRP) and steel tendons. A finite element model has been developed and is validated against the available test data. A numerical test is carried out on two-span continuous bonded prestressed concrete beams. Three types of tendons are considered for a comparative study: aramid FRP (AFRP), carbon FRP (CFRP) and prestressing steel. Various levels of ωp (reinforcement index of prestressing tendons) are used. The results indicate that, with increasing ωp, the failure mode of FRP prestressed concrete beams would transit from tendon rupture to concrete crushing while the crushing failure always takes place in steel prestressed concrete beams. Moreover, FRP tendons mobilize significantly different behavior regarding the crack pattern, deformation characteristics and neutral axis depth compared to steel tendons. The moment redistribution at ultimate in AFRP prestressed concrete beams is comparable to that in steel prestressed concrete beams while, at a low ωp level, CFRP tendons register obviously lower redistribution than steel tendons.